The importance of modeling epileptic seizure dynamics as spatio-temporal patterns - Baier, Gerold; Goodfellow, Marc; Taylor, Peter N.; Wang, Yujiang; Garry, Daniel J. (Frontiers in Physiology, 2012)
The occurrence of seizures is the common feature across the spectrum of epileptic disorders. We describe how the use of mechanistic neural population models leads to novel insight into the dynamic mechanisms underlying two important types of epileptic seizures. We specifically stress the need for a spatio-temporal description of the rhythms to deal with the complexity of the pathophenotype. Adapted to functional and structural patient data, the macroscopic models may allow a patient-specific description of seizures and prediction of the impact of specific interventions.